EFEKTIFITAS MEDIA BUKU AJAR BERBASIS QR CODE (QUICK RESPONSE CODE) DALAM PEMBELAJARAN MAHARAH KALAM BAGI MAHASISWA - Dea Annisa Fitri; Aufia Aisa (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2023)
Creative and innovative media in the form of QR Code-based Arabic textbooks aim to eliminate the monotony and boredom of students and make it easier for students to learn Arabic lessons, especially in Maharah Kalam. The research method used is Research and Development (R&D) with a development model from Borg and Gall which consists of 10 stages. Research instruments include observation, interviews, surveys and testing. The research data are in the form of expert questionnaires and respondent questionnaires, which are analyzed through evaluation indicators. According to the findings of this study, the QR Code-based textbook products are grouped by: hiwar, mufrodat, istima', qiro'ah, kalam, and kitabah. QR Codes are present in the hiwar, mufrodat, and istima' sections. With chapter boundaries and illustrative images for ease of understanding. 2) Very feasible, The media validation questionnaire score of 88.8% and the material validation questionnaire score of 94% are both feasible, with excellent criteria. 3) Based on the results of the Wilcoxon test, learning becomes very effective because of positive changes for students. So it can be concluded that with this media students are more interested and even easier to learn Arabic and its maharah especially maharah kalam.